Day and night surgery: Comparing outcomes in deceased donor renal transplant with surgeons' perspectives to operate at odd hours - a prospective observational study - Ketan Mehra; Ramanitharan Manikandan; Lalgudi Narayanan Dorairajan; Kodakkattil Sreenivasan Sreerag; Rajiv Kumar (Indian Journal of Transplantation, 2020)
Introduction: Working in stress during night may be hazardous to the patients as well as professionals. The aim of the present study was to compare the outcomes of emergency renal transplants performed during the day with those during the night. Materials and Methods: The data of deceased transplants performed between March 2012 and June 2018 was reviewed retrospectively. Group 1 included patients operated between 8 am and 8 pm while Group 2 patients were operated between 8 pm and 8 am. The outcomes compared included cold ischemia time, vascular and urologic complications, creatinine over time period, graft survival, and mortality, if any. A custom-designed questionnaire was distributed to surgeons covering the practice of urgent renal transplant, including fatigue. Results: A total of 71 transplant recipients were included in this study. Forty (56.3%) belonged to Group 1 and 31 (43.7%) to Group 2. There were no significant differences with respect to complications, renal graft function, and patient survival between day and night time surgeries. Conclusion: Emergency renal transplants during night hours do 'not have inferior outcomes in comparison to patients operated during day time. The majority of surgeons feel less proficient in performing surgery during emergency hours and given a choice would prefer to operate during the subsequent elective operating hour.